A Critical Overview of FDA and EMA Statistical Methods to Compare In Vitro Drug Dissolution Profiles of Pharmaceutical Products - Muselik, Jan; Komersová, Alena; Kubova, Katerina; Matzick, Kevin; Skalická, Barbora (MDPI, 2021)
A drug dissolution profile is one of the most critical dosage form characteristics with immediate and controlled drug release. Comparing the dissolution profiles of different pharmaceutical products plays a key role before starting the bioequivalence or stability studies. General recommendations for dissolution profile comparison are mentioned by the EMA and FDA guidelines. However, neither the EMA nor the FDA provides unambiguous instructions for comparing the dissolution curves, except for calculating the similarity factor f(2). In agreement with the EMA and FDA strategy for comparing the dissolution profiles, this manuscript provides an overview of suitable statistical methods (CI derivation for f(2) based on bootstrap, CI derivation for the difference between reference and test samples, Mahalanobis distance, model-dependent approach and maximum deviation method), their procedures and limitations. However, usage of statistical approaches for the above-described methods can be met with difficulties, especially when combined with the requirement of practice for robust and straightforward techniques for data evaluation. Therefore, the bootstrap to derive the CI for f(2) or CI derivation for the difference between reference and test samples was selected as the method of choice.
kritický přehled FDA a EMA statistických metod pro srovnání in vitro disolučních profilů farmaceutických produktů
Keywords: drug dissolution; dissolution profile comparison; EMA and FDA strategy; disoluce léčiv; srovnání disolučních profilů; EMA a FDA strategie